Synthesis of carboxymethyl starch-g-polyvinylpyrolidones and their properties for the adsorption of Rhodamine 6G and ammonia. (15th April 2018) - Haroon, Muhammad; Wang, Li; Yu, Haojie; Ullah, Raja Summe; Zain-ul-Abdin,; Khan, Rizwan Ullah; Chen, Qing; Liu, Jian
Highlights: Carboxymethyl starch- g -polyvinylpyrolidones were prepared. CMS- g -PVP-5 had the maximum grafting percentage and grafting efficiency. CMS- g -PVP-5 showed excellent adsorption efficiency. Abstract: Carboxymethyl starch- g -polyvinylpyrolidones (CMS- g -PVPs) were prepared by grafting of carboxymethyl starch (CMS) with N -vinylpyrolidone (NVP) using different initiators. The grafting percentage of all the modified starches was determined and the modified starch (CMS- g -PVP-5) with maximum grafting percentage was characterized by elemental analysis, 1 H NMR and FT-IR spectroscopy. Crystallinity and thermal properties of CMS- g -PVP-5 were analysed by XRD and TGA, respectively. CMS- g -PVP-5 was then utilized for the adsorption of Rhodamine 6G (dye) from water under different p H, temperature, adsorbate doze and adsorbent concentration. This modified starch showed good adsorption ability towards Rhodamine 6G. CMS- g -PVP-5 was also applied for the adsorption of ammonia gas and proved an exciting adsorbent for ammonia.